Let Me Make You Happy, and I'll Tell You How You Look Around: Using an Approach-Avoidance Task as an Embodied Emotion Prime in a Free-Viewing Task - Czeszumski, Artur; Albers, Friederike; Walter, Sven; König, Peter (Frontiers in Psychology, 2021)
The embodied approach of human cognition suggests that concepts are deeply dependent upon and constrained by an agent’s physical body’s characteristics, such as performed body movements. In this study, we attempted to broaden previous research on emotional priming, investigating the interaction of emotions and visual exploration. We used the joystick-based approach-avoidance task to influence the emotional states of participants, and subsequently, we presented pictures of news web pages on a computer screen and measured participant’s eye movements. As a result, the number of fixations on images increased, the total dwell time increased, and the average saccade length from outside of the images towards the imagesdecreased after the bodily congruent priming phase. The combination of these effects suggests increased attention to web pages’ image content after the participants performed bodily congruent actions in the priming phase. Thus, congruent bodily interaction with images in the priming phasefosters visual interaction in the subsequent exploration phase.